2020
DOI: 10.1097/jcn.0000000000000637
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of Cardiovascular Risk Factors and Their Impact on the 20-Year Cardiovascular Risk in a General Population

Abstract: Background Clustering of cardiovascular risk factors (CVRFs) is extraordinarily common and is associated with an increased risk of cardiovascular disease (CVD). However, the particular impact of the sum of CVRFs on cardiovascular morbidity and mortality has not been sufficiently explored in Europe. Objective The aim of this study was to analyze the differences in survival-free probability of CVD in relation to the number of CVRFs in a Spanish population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…ALDH2 activation has also been found to be associated with improved mitochondrial function and the remodeling of ventricular function [14,15], and many studies have reported an association between ALDH2 and CVDs [1,2,5,13,15,16]. The most important known feature of the myocardial cardio-protective role of ALDH2 is the clearance of toxic aldehydes such as 4-hydroxynonenal and its adducts, which can be induced by acute oxidative stress upon cardiac ischemia or reperfusion [17][18][19].…”
mentioning
confidence: 99%
“…ALDH2 activation has also been found to be associated with improved mitochondrial function and the remodeling of ventricular function [14,15], and many studies have reported an association between ALDH2 and CVDs [1,2,5,13,15,16]. The most important known feature of the myocardial cardio-protective role of ALDH2 is the clearance of toxic aldehydes such as 4-hydroxynonenal and its adducts, which can be induced by acute oxidative stress upon cardiac ischemia or reperfusion [17][18][19].…”
mentioning
confidence: 99%
“…Weight loss in obese people is a modifiable aspect that reduces other cardiovascular risk factors. 24 The level of adherence in both exercise groups was 95%, slightly higher than 93.1% reported after 8 weeks of MICT in overweight and obese adults, 25 and 12-week MIIT programs (91.7%). 26 No participants included in this study presented adverse effects or complications due to participation in this program.…”
Section: Discussionmentioning
confidence: 70%
“…A greater number of cardiovascular risk factors have been associated with a higher risk of total cardiovascular morbidity and mortality. Weight loss in obese people is a modifiable aspect that reduces other cardiovascular risk factors 24 …”
Section: Discussionmentioning
confidence: 99%
“…26,27 This clearly shows that individuals with 1 or more CVD risk factors are at increased risk for CVD morbidity and mortality for each additional CVD risk factor. 28 Nevertheless, hypertension was found to have the greatest likelihood for adverse childbirth outcomes, a finding that is amplified by most cohort, population-based, and randomized controlled trial studies. 29 This indicates the need for heightened antenatal surveillance of women with hypertension and other CVD risk factors to detect any adverse pregnancy complications and to improve CVH from preconception and throughout a woman's lifespan.…”
Section: Discussionmentioning
confidence: 99%